A Retrospective Analysis Investigating Whether Case Volume Experience of the Anesthesiologist Correlates with Intraoperative Efficiency for Joint Arthroplasty. - Macias, Alvaro A.; Bongbong, Dale N.; Waterman, Ruth S.; Simpson, Sierra; Gabriel, Rodney A. (Journal of Medical Systems, 2023)
The objective of this retrospective study was to determine if there was an association between anesthesiology experience (e.g. historic case volume) and operating room (OR) efficiency times for lower extremity joint arthroplasty cases. The primary outcome was time from patient in the OR to anesthesia ready (i.e. after spinal or general anesthesia induction was complete). The secondary outcomes included time from anesthesia ready to surgical incision, and time from incision to closing completed. Mixed effects linear regression was performed, in which the random effect was the anesthesiology attending provider. There were 4,575 patients undergoing hip or knee arthroplasty included. There were 82 unique anesthesiology providers, in which the median [quartile] frequency of cases performed was 79 [45, 165]. On multivariable mixed effects linear regression – in which the primary independent variable (anesthesiologist case volume history for joint arthroplasty anesthesia) was log-transformed – the estimate for log-transformed case volume was − 0.91 (95% confidence interval [CI] -1.62, -0.20, P = 0.01). When modeling time from incision to closure complete, the estimate for log-transformed case volume was − 2.07 (95% -3.54, -0.06, P = 0.01). Thus, when comparing anesthesiologists with median case volume (79 cases) versus those with the lowest case volume (10 cases), the predicted difference in times added up to only approximately 6 min. If the purpose of faster anesthesia workflows was to open up more OR time to increase surgical volume in a given day, this study does not support the supposition that anesthesiologists with higher joint arthroplasty case volume would improve throughput.